Confined silicon nanospheres by biomass lignin for stable lithium ion battery. (12th September 2017) - Niu, Xiaoying; Zhou, Jinqiu; Qian, Tao; Wang, Mengfan; Yan, Chenglin
Abstract: Biomass lignin, as a significant renewable resource, is one of the most abundant natural polymers in the world. Here, we report a novel silicon-based material, in which lignin-derived functional conformal network crosslinks the silicon nanoparticles via self-assembly. This newly-developed material could greatly solve the problems of large volume change during lithiation/delithiation process and the formation of unstable solid electrolyte interphase layers on the silicon surface. With this anode, the battery demonstrates a high capacity of ∼3000 mA h g −1, a highly stable cycling retention (∼89% after 100 cycles at 300 mA g −1 ) and an excellent rate capability (∼800 mA h g −1 at 9 A g −1 ). Moreover, the feasibility of full lithium-ion batteries with the novel silicon-based material would provide wide range of applications in the field of flexible energy storage systems for wearable electronic devices.